Impacto del uso de los drones para realizar aspersiones en plantaciones de maíz (Zea mays) - Vera Acosta, Juan José (2022)
Precision agriculture originated as a set of practices used by farmers to manage crop fertilization using drone technology to reduce the excessive use of foliar products, thus saving money and reducing environmental damage. That is why, the present research offers an approach to the impact of the use of drones in spraying on corn crops, scientific, academic publications, books and theses were examined. Therefore, it is convenient to highlight that drones can fly at short distances from the ground, allow rapid detection and transfer of information to the user, since the collection of data is necessary to calculate the variable rate of fertilization, this information is obtained mainly through yield maps, soil mapping and mobile sensors. Therefore, in summary, using drones for corn crop monitoring is too useful, as they can acquire high-resolution images in different wavebands. The multispectral or RGB channel images can be converted into vegetation indices such as Normalized Difference Vegetation Index (NDVI) and Wide Dynamic Range Vegetation Index (WDRI). These indices can effectively distinguish living plants from the ground, which is critical for determining early season plant spacing. Several types of multispectral indices are now available, which can help capture crop variability with respect to nitrogen contributions and yield.